ANALISIS TEKNIK TERJEMAHAN FOLKLOR SUNDA ‘TALAGA WARNA’ (Transformasi Antarbahasa: Bahasa Indonesia – Jepang) - Nurohmah, Hety (IZUMI, 2016)
[Title: English translation of Sundanesse folklore 'Talaga Warna' (Interlanguage Transformation: Indonesian – Japanese)] This study reviews translated text of Sunda’s folklore entitled ‘Talaga Warna’ that has translated from Indonesian into Japanese. The object of this study was analyzed by using method of translation techniques according to Moentaha’s theory (2016). The results of this study are description of translation techniques that used in translation process of folklore Sunda 'Talaga Warna' . Translation techniques were using replacement techniques words into clauses, replacement of lexical and word classes, addition of conjunctions and adverbs, omission of words and pronouns, compression/solids, and paraphrasing gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor